2009
DOI: 10.1038/nature07927
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between NPY and neuroticism?

Abstract: Psychiatric genetics has been hampered by the fact that initially exciting findings from underpowered studies are so often not replicated in larger, more powerful, data sets. Here we show that the claims of Zhou et al. that neuropeptide Y (NPY) diplotype-predicted expression is correlated with trait anxiety (neuroticism) is not replicated in a data set consisting of phenotypically extreme individuals drawn from a large (n = 88,142) non-clinical population. We found no association between NPY diplotype or diplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…21, 22, 23, 24, 25, 26, 27 Candidate studies have reported associations with markers within several genes, 28, 29, 30, 31, 32 but again, replication generally failed. 33, 34, 35 To date, a number of genome-wide association studies (GWAS) for higher-order personality traits have been published. 36, 37, 38, 39, 40 None of them, however, has reported genome-wide significant associations between neuroticism/extraversion and markers.…”
Section: Introductionmentioning
confidence: 99%
“…21, 22, 23, 24, 25, 26, 27 Candidate studies have reported associations with markers within several genes, 28, 29, 30, 31, 32 but again, replication generally failed. 33, 34, 35 To date, a number of genome-wide association studies (GWAS) for higher-order personality traits have been published. 36, 37, 38, 39, 40 None of them, however, has reported genome-wide significant associations between neuroticism/extraversion and markers.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been suggested that polymorphisms in the NPY gene predict individual differences in stress response and emotionality. Thus, genetically induced lower NPY expression may result in higher emotion-induced activation of the amygdala (Zhou et al, 2008, but see also Cotton et al, 2009), development of major depression (Mickey et al, 2011), as well as lower NPY plasma levels (Xu et al, 2012, but see also Nishi et al, 2014). Furthermore, a functional NPY variation was suggested to cause lower NPY mRNA expression in the amygdala and reduced cerebrospinal fluid (CSF)-NPY A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 9 levels in higher primates exposed to aversive situations (Lindell et al, 2010).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In a genome-wide study of US-based and German samples, van den Oord [28] found association between neuroticism and four SNPs in the chr 14 gene MAMDC1 (combined p <10 −6 ). To date, the most recent association study [29] failed to replicate an association between the candidate gene NPY and stress response and emotion (reported by Zhou [30], using instruments other than the EPQ).…”
Section: Introductionmentioning
confidence: 99%